2016
DOI: 10.1007/s12155-016-9733-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Composition and Underlying QTL in an F1 Pseudo-Testcross Population of Switchgrass

Abstract: Natural genetic variation for reduced recalcitrance can be used to improve switchgrass for biofuel production. A full-sib switchgrass mapping population developed by crossing a lowland genotype, AP13, and upland genotype, VS16, was evaluated at three locations (Ardmore and Burneyville, OK and Watkinsville, GA). Biomass harvested after senescence in 2009 and 2010 was evaluated at the National Renewable Energy Laboratory (NREL) for sugar release using enzymatic hydrolysis and for lignin content and syringyl/guai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Our report extends this observation as a general trend affecting all transgenic and control switchgrass lines studied within BESC. This trend towards increased recalcitrance in switchgrass tissue over years was also observed in native population studies (Serba et al, 2016).…”
Section: Recalcitrance Reductions Indicated By Bioconversion To Ethanolsupporting
confidence: 77%
“…Our report extends this observation as a general trend affecting all transgenic and control switchgrass lines studied within BESC. This trend towards increased recalcitrance in switchgrass tissue over years was also observed in native population studies (Serba et al, 2016).…”
Section: Recalcitrance Reductions Indicated By Bioconversion To Ethanolsupporting
confidence: 77%
“…QTL with positive additive effects for postharvest regrowth were reported on chromosome 5N (5b) of a switchgrass biparental population, Kanlow-K5×Alamo-A4 (Lowry et al, 2015). Linkage map from the same pseudo-F 1 testcross population was constructed using SSR, STS, and DArT markers, and QTL for biomass yield, plant height, and recalcitrant traits were identified (Serba et al, 2015(Serba et al, , 2016(Serba et al, , 2013.…”
mentioning
confidence: 99%
“…The current study identified six QTLs for HT, CD, or PB using a pseudo-F 2 population of switchgrass. The number of identified QTLs in this study was smaller than some previous studies [14][15][16][17][18][19]. The variations in QTL numbers in different studies could be due to varied mapping populations (e.g., F 1 or F 2 crosses made by lowland × lowland or lowland × upland genotypes), and a number of traits and environments assessed for the population.…”
Section: Discussionmentioning
confidence: 55%
“…Such relationships provide insights into the genetic control of a trait of interest, as well as providing a mechanism to improve the efficiency of a breeding program. When multiple QTLs are identified as genetic components explaining variation of a trait, the trait is typically referred to as Bcomplex.^Toward this end, QTLs for tillering, plant height, flowering time, cell wall composition, and biomass yield have been detected across a variety of studies and mapping populations in switchgrass [13][14][15][16][17][18][19][20]. For example, a high number of QTL on chromosome 5a (20 QTLs) and 2a (26 QTLs) for six tillering-related traits assessed in 2 years at two locations have been identified in a lowland full-sib F 1 mapping population and a selfed population, respectively [18].…”
Section: Identification Of Quantitative Trait Loci For Plant Height mentioning
confidence: 99%
See 1 more Smart Citation